Validity and reliability of meaning pressure pain threshold using WE pressure pain threshold meter in diabetic foot of type 2 diabetes mellitus patients - Srimuang, Nutthakarn; Chatchawan, Uraiwan; Peungsuwan, Pannee; Donpunha, Wanida; Eungpinichpong, Wichai (Archives of Allied Health Sciences, 2019)
Sensory impairment or numbness in both feet is the most common complication in diabetic patient caused by peripheral neuropathy and arterial disease. Traditional Thai massage (TTM) is the one of the alternative treatments for diabetic feet. Mostly, the amount of massage-pressing pressure for a diabetic patient tends to higher than healthy person. Applying the over pressing pressure may lead to tissue damage. Therefore, to specify the safety and efficacy of the pressing pressure is importance. However, no study conducts the instrument that to be modified for measuring the pressing pressure before. Therefore, the study aimed to examine the validity and reliability of a new instrument entitled WE pressure pain threshold meter. The digital force gauge and a digital algometer were selected as a standard instruments. The reliability test was done in 43 diabetic patients with age of 64.77 ± 8.41 years, and 65.1 % of female. Each patient was applied the pressing pressure on the point between the 2nd and 3rd head of metatarsal bones of the dominant foot. The pressing pressure was maintain for 5 sec by gentle and slightly increase pressure until the patient start to feel some discomfort (sub-pain threshold). It was repeated 3 times with 2-min rest between repetitions. Results found that WE algometer presented a high validity by reporting the 2-similar Pearson’s correlation coefficient which was 0.99 (95% CI of 0.99 to 1.00 and P < 0.001) and a high reliability that the Intraclass Correlation Coefficient (ICC) was 0.87 (95% CI 0.78 to 0.93, P < 0.001). In conclusion, WE algometer has excellent validity and high reliability. It is also simply for applying and inexpensive. Therefore, it could be used as the instrument for the follow up assessment after physical therapy, traditional Thai massage, and future researches.